Pertanggungjawaban Pidana dan Manajemen Operasional Dalam Risiko Konsumen Pada Platform E-Commerce Berbasis Ai - Rahmawati, Apitta Fitria; Naili, Yuris Tri (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
The rapid development of artificial intelligence (AI) on e-commerce platforms brings new risks for digital consumers that Indonesian criminal law has not fully addressed, especially when algorithmic decisions cause harm without a clear human actor. This article assesses the effectiveness of Indonesian criminal law in protecting digital consumers and evaluates the role of internal operational management such as fraud detection, data protection, and algorithm governance in risk mitigation. Using a normative-juridical method and comparative analysis, the research identifies legal gaps regarding criminal liability for damages caused by AI systems (liability gap), and also demonstrates the limitations of the mens rea principle in the algorithmic context. This article proposes an integrative model that combines criminal rule reforms to clarify corporate and developer liability and mandatory operational governance standards (compliance by design) to enhance prevention, detection, and recovery. The findings confirm the need for regulatory and operational synergy to strengthen digital consumer protection in an increasingly autonomous digital market era.